(untitled) (CIPEEX, 2025)
This article examines the temporal milestone for the definitive constitution of a tax credit for purposes of the statute of limitations, arguing that the taxpayer’s notification of the notice of infraction both perfects the assessment and starts the five-year limitation period for collection, thereby excluding any decadential period once the assessment has been made. The objective is to delimit, within the context of ex officio assessment, the moment from which the limitation period runs and to assess the implications of that definition for legal certainty and fiscal stability. The method is doctrinal and case-law oriented, combining a literature review with a critical analysis of competing views that place the constitution of the credit at the notification to pay/challenge, at first- or second-instance administrative decisions, at the final unappealable administrative decision, or at enrollment in the registry of outstanding debts. The results map these strands and show that, by its nature, the notice of infraction is deemed constituted upon valid notification to the taxpayer, from which the five-year limitation period begins to run; once constituted, the credit is no longer subject to decadence, which is confined to the pre-assessment stage. The conclusion is that adopting this temporal marker enhances clarity and predictability, focuses post-assessment extinction on limitation, and reduces uncertainty about enforceability, while upholding legality and legal certainty.